ERROR ANALYSIS ON THE GRAMMATICAL USAGE FOUND IN HORTATORY EXPOSITION PARAGRAPHS BY ELEVENTH GRADE ACCELERATION STUDENTS AT SMA NEGERI 1 LAWANG - AGUSTIN, KURNIA TRI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: error analysis, error, hortatory exposition paragraphs, kinds of errors.English is one of international languages in this world. It plays an important role in every aspect of modern life such as education, politics,economics and science. In Indonesia, English becomes a subject of education inschools and universities. In the process of learning, Indonesian learners may make errors. It is natural because English and Indonesian have different grammatical rules.In this study, the researcher examines (1) the kinds of errors in the pre-testand post-test and (2) the differences result in the number of errors in the pre-test and post-test found in hortatory exposition paragraphs by acceleration students.The researcher uses descriptive qualitative approach and document analysis inorder to answer the research problems. In this research, the researcher classifiesthe errors based on Dulay’s theory. The data are 14 hortatory expositionparagraphs in the pre-test and 14 hortatory exposition paragraphs in the post-test made by eleventh grade acceleration students of SMA Negeri 1 Lawang. In data collection in the pre-test, the researcher provides writing with a topic provided and gave 90 minutes to finish their hortatory exposition paragraphs. The researcher gives a test again at least one month after pre-test to collect data for the post-test. The researcher gives the same topic and the students are asked to write a hortatory paragraphs with same topic in pre-test.The writer finds errors appear in various kinds of cases, such as omissionthat was divided into five. They were omission of article, omission of preposition,omission of noun/pronoun, omission of verb and omission of plural marker. Then, addition was divided into three. They were regularization, double marking and simple addition. Also misformation was divided into six. They were misformation of plural marker, misformation of verb, misformation of noun, misformation ofbe, misformation adjective and misformation of preposition. The last was misordering. The total number of errors is 190 errors in the pre-test and 144 errors in the post-test.The researcher suggests the next researcher who wants to conduct a similarresearch use another theory or the same theory and give not only one pre-test and post-test but also give more test to know the progress of the students deeply.